Teacher Preparedness and Practices of Inquiry Based Instruction in School Science - Paudel, Mohan (Education and Development, 2020)
The study was carried out with the purpose to dig out science teachers’ perspectives and practices of inquiry based science instruction at basic level of institutional and community schools in Kathmandu district. Furthermore, teacher preparedness, school facilities, administrative support and mechanism to support students’ learning through inquiry based instruction were evaluated. A quantitative survey design was applied to collect data from randomly selected 36 science teachers teaching science at grade eight in the selected schools. Data were collected using pretested questionnaire containing Likert scale type items and open ended questions. Teacher, student, curriculum and school-related factors were found as major affecting factors in practice of inquiry based instruction in schools. Science teachers concerned more about facility related issues rather than pedagogical practices. Some factors including teachers’ low level of confidence, inadequate knowledge and little experience in conducting inquiry based instruction, insufficient school facilities and resources, tight curriculum demanding little inquiry were identified which hindered the implementation of inquiry based approach in science instruction. Moreover, traditional teaching practices, over emphasis on exam are additional factors hindering the practice of inquiry based teaching. It is recommended that inquiry approach should be incorporated in student teaching, science curriculum framing, science teacher professional development programs, classroom management and student evaluation.